A kind of EVA light-converting packaging film and preparation method thereof
By using homemade zeolite-rare earth light converter in EVA packaging materials, the problem of EVA material aging and yellowing in outdoors is solved, the photoelectric conversion efficiency of solar cells is improved, and it has excellent anti-PID performance and long-term stability.
Patent Information
- Application Number
- CN202410672305.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-28
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-05-28
AI Technical Summary
Existing EVA packaging materials are prone to aging and yellowing when used in harsh outdoor climates, resulting in reduced photoelectric conversion efficiency or short circuit damage, and the use of ultraviolet absorbers will lose ultraviolet light energy.
An EVA convertible encapsulation film was designed. Through a homemade convertible agent, the convertible agent uses zeolite to exchange ion with rare earth ions, and combines large molecules and small molecules organic ligands for coordination reaction to form a high fluorescence intensity. and good compatibility with light converter.
It improves the photoelectric conversion efficiency of solar cells, avoids the damage of ultraviolet light on the EVA film, and has excellent anti-PID performance and long-term stability.
Smart Images

Figure BDA0004863043550000201
Abstract
Description
Technical Field
[0001] The invention relates to an EVA light-converting packaging film and a preparation method thereof, and belongs to the field of photovoltaic materials. Background Art
[0002] EVA (ethylene-vinyl acetate copolymer) is a thermoplastic polymer material. As a solar cell packaging material, it has many advantages, including low cost, easy molding, outstanding optical properties, excellent mechanical properties and electrical properties. Nearly 30 years of use have proved that EVA packaging materials can basically work stably for 10 years. However, if used for a longer period of time in harsh outdoor climate environments, EVA will age and yellow, resulting in a decrease in the photoelectric conversion efficiency of the battery components or short circuit damage and failure. Ultraviolet aging is precisely the main factor causing the yellowing of EVA film. The current technology is to add ultraviolet absorbers to EVA to reduce the damage of ultraviolet rays to EVA film. The addition of ultraviolet absorbers converts ultraviolet light into low-energy heat energy that cannot be used by solar cells, resulting in the loss of light energy and reducing the efficiency of solar cells.
[0003] The significance of the existence of light conversion film is very important. The core of light conversion film is light conversion agent, which mainly includes organic fluorescent materials, rare earth organic complexes and rare earth inorganic compounds. Rare earth organic complexes are an important type of light conversion agent at present. Rare earth organic complexes have the advantages of both good stability of inorganic materials and high fluorescence quantum efficiency of organic materials, and are luminescent materials with broad application prospects. However, rare earth organic complexes have problems such as poor compatibility with matrix resin, quenching between fluorescent molecules, oxidation and decomposition, reduced service life, weakened light transmittance, and reduced efficiency of light energy absorption and conversion.
[0004] Therefore, it is necessary to design a new type of light-converting film, whose structure and molecular weight are similar to those of the polymer matrix, so as to enhance its dispersibility and compatibility. And it has good stability and is not prone to oxidation and decomposition, so as to solve the shortcomings and deficiencies of the existing technology. Summary of the invention
[0005] The purpose of the present invention is to provide an EVA light conversion packaging adhesive film and a preparation method thereof to solve the problems of rare earth light conversion agents in the prior art, such as poor thermal stability during high-temperature processing, poor long-term stability of hydrolysis and oxidation in long-term outdoor use, and poor dispersibility in EVA resin. The present invention prepares a light conversion agent by molecular design and through formula design, while overcoming the above problems, it also has excellent anti-PID performance and has broad application potential. The technical solution adopted by the present invention to solve its technical problems is:
[0006] A method for preparing a light conversion agent comprises the following steps:
[0007] S11, performing an ion exchange reaction between zeolite and rare earth ions to obtain an intermediate product I;
[0008] S12, coupling the hydroxy aromatic acid with the olefin structure A to obtain an intermediate product II;
[0009] S13, subjecting the intermediate product II to acrylamide for free radical polymerization to obtain an intermediate product III, i.e., the first ligand;
[0010] S14, performing coordination reaction on the intermediate product I, the first ligand, and the second ligand to obtain an intermediate product IV; and
[0011] S15, coupling reaction of the intermediate product IV with the olefin-containing structure B to obtain the target product, i.e., the light conversion agent.
[0012] Furthermore, the zeolite and the rare earth ions are added in a molar ratio of sodium ions to rare earth ions of 20-30:1.
[0013] Furthermore, the rare earth ions are europium ions and other rare earth ions in a molar ratio of 2.0-3.0:7.0-8.0; and
[0014] The particle size of the zeolite is 0.1-1.0 μm.
[0015] Furthermore, the other rare earth ions include yttrium ions or cerium ions.
[0016] Furthermore, the olefinic structure A is an olefinic compound containing a group that can react with a hydroxyl group.
[0017] Furthermore, the molar ratio of the intermediate product II to acrylamide is 0.3-0.6:0.7-0.4.
[0018] Furthermore, the first ligand and the second ligand are added at a molar ratio of 2-4:1 in terms of the coordination structure; and
[0019] The intermediate product I is added in a ratio of the first ligand to the second ligand according to a molar ratio of the rare earth ion to the structure participating in the coordination of 1:8-10.
[0020] Furthermore, the second ligand includes a pyridine derivative containing active hydrogen.
[0021] Furthermore, the olefin-containing structure B is a substance that can react with active hydrogen groups and contains olefins.
[0022] Another object of the present invention is to provide a light conversion agent prepared by a preparation method.
[0023] Another object of the present invention is to provide an EVA light-converting packaging film, comprising the following raw materials in parts by weight:
[0024] EVA resin 100 parts;
[0025] Cross-linking agent 0.8-1.2 parts;
[0026] 1.0-1.5 parts of auxiliary cross-linking agent;
[0027] 0.1-5.0 parts of light conversion agent;
[0028] Antioxidant 0.15-0.25 parts;
[0029] Light stabilizer 0.05-0.08 parts;
[0030] Coupling agent 0.3-0.5 parts.
[0031] Another object of the present invention is to provide a method for preparing an EVA light-converting packaging film, comprising the following steps:
[0032] S21, mixing, i.e.
[0033] Adding raw materials into a mixer according to the formula ratio, mixing and stirring to obtain mixed raw materials;
[0034] S22, extrusion, i.e.
[0035] placing the mixed raw materials in S21 in an extruder for melt blending, extrusion, casting, and cooling; and
[0036] S23, film formation, i.e.
[0037] After thickness measurement, edge pressing, shaping, edge trimming and rolling, the EVA light-converting packaging film is obtained.
[0038] Beneficial effects of the present invention:
[0039] (1) The present invention provides an EVA light-converting encapsulating film, wherein the formula system contains a self-made light-converting agent, which is a rare earth organic complex structure with zeolite as a carrier; wherein the rare earth structure has europium ions as the core and yttrium or cerium ions as sensitizing ions; the first ligand is a macromolecular chain containing aromatic acid and amide structures; and the second ligand is a structure containing pyridine. First, zeolite is a porous inorganic salt structure with high heat resistance, which can give rare earth ions thermal stability during thermal processing; second, the porous structure of zeolite gives rare earth ions a larger specific surface area, which is convenient for coordination reaction with organic ligands; third, the unique cage structure of zeolite can play a good protective role, is not easy to hydrolyze or oxidize, has long-term stability, and can improve energy transfer; fourth, yttrium or cerium ions are used as sensitizing ions, and have greater fluorescence intensity when combined with europium; fifth, the first ligand, on the one hand, acts as an excellent ligand to transfer energy to rare earth ions; on the other hand, it wraps the zeolite, eliminates phase separation and provides better dispersibility; sixth, pyridine is an excellent ligand for rare earth ions, and its small molecular structure can easily enter zeolite to form better coordination, thereby improving energy transfer efficiency; at the same time, pyridine derivatives have reactive groups that can be used as reaction sites for the next step; seventh, the porous structure of zeolite, the coordination function of rare earth ions, and the alkaline structure of polyamide can adsorb free acetic acid produced by EVA deterioration, and have anti-aging and anti-PID properties.
[0040] (2) The present invention provides an EVA light-converting encapsulation film, which converts ultraviolet light that is originally lost due to absorption by ultraviolet light absorbers into visible light for utilization, thereby improving the photoelectric conversion efficiency of solar cells and avoiding the damage of ultraviolet light to the base material EVA film, which has great practical significance.
[0041] (3) The present invention provides a method for preparing an EVA light-converting encapsulating film. The light-converting agent in the formula system is prepared using common raw materials, and the use of yttrium or cerium and europium to form a double rare earth organic complex has a higher cost-effectiveness and also has the effect of an auxiliary light stabilizer, which is conducive to the industrialization of the product of the present invention and has strong operability. DETAILED DESCRIPTION
[0042] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0043] The purpose of the present invention is to develop an EVA light-converting encapsulation film to meet the application requirements of existing photovoltaic encapsulation materials. The idea of realization is: to make a self-made light-converting agent to ensure its compatibility and dispersibility in EVA while having high stability and high fluorescence intensity. Specifically: in view of the excellent fluorescence properties of rare earth materials, the rare earth materials are molecularly designed: first, considering the concentration effect of rare earth ions, rare earth ion complex sensitization is used to improve the fluorescence performance of the light-converting machine; second, the zeolite structure cage structure has a good protective effect on rare earth ions; at the same time, the fluorescence intensity can be improved; third, the organic ligands of rare earth ions are designed and selected, and the compatibility of the light-converting agent and the matrix can be improved while improving the fluorescence performance, and the optical performance is improved. The theoretical basis for realization is: after the rare earth ions and zeolites are ion-exchanged, the macromolecular organic ligands and small molecule organic ligands (containing active hydrogen) are used for coordination, and after the coordination is completed, the small molecule ligands are coupled to form a double bond structure. The above-mentioned light-converting agent structures synergize with each other and have excellent compatibility with the matrix, stability, fluorescence performance, etc. Embodiments of the present invention are as follows:
[0044] The present invention provides a method for preparing a light conversion agent, comprising the following steps:
[0045] S11, adding zeolite into a deionized water solution containing rare earth ions, stirring, heating to 70-90°C and reacting for 20-30 hours; after the reaction, filtering, taking out insoluble matter, rinsing with deionized water A, and drying at 60°C for 12 hours to obtain an intermediate product I;
[0046] The zeolite and rare earth ions are added in a molar ratio of sodium ions to rare earth ions of 20-30:1;
[0047] The concentration of the deionized water solution containing rare earth ions is 0.03-0.05 mol / L;
[0048] The dosage of the zeolite and deionized water A is 1 g:100 mL.
[0049] The rare earth ions are europium ions and other rare earth ions in a molar ratio of 2.0-3.0:7.0-8.0; and
[0050] The other rare earth ions include yttrium ions or cerium ions.
[0051] The anions in the rare earth compound to which the rare earth ions belong may be chloride ions, nitrate ions, etc., and preferably chloride ions. The rare earth ions described in the following embodiments of the present invention are rare earth ions provided by chloride salts.
[0052] The zeolite has a particle size of 0.1-1.0 μm; it may be X-type zeolite, Y-type zeolite, chabazite, mordenite, P-type zeolite, etc.; and the zeolite described in the following embodiments of the present invention is X-type zeolite.
[0053] S12, adding hydroxy aromatic acid and acid binding agent to dichloromethane A, stirring, adding olefin structure A, controlling the temperature, reacting for 4-12 hours; filtering, taking the filtrate, washing with 20wt% dilute hydrochloric acid and deionized water B for 3 times respectively, separating the liquids, taking the organic phase, drying with anhydrous sodium sulfate, standing overnight, filtering, taking the organic phase, and rotary evaporating to obtain intermediate II;
[0054] The dosage ratio of the hydroxyaromatic acid, dichloromethane A, 20wt% dilute hydrochloric acid, deionized water B, and anhydrous sodium sulfate is 1mmol:100mL:150mL, 150mL:10g;
[0055] The hydroxy aromatic acid may be 6-hydroxy-2-naphthoic acid, 2-hydroxymethylbenzoic acid, m-hydroxybenzoic acid, p-hydroxybenzoic acid, 3-amino-4-methylbenzoic acid, 5-amino-isophthalic acid, etc.; and 6-hydroxy-2-naphthoic acid is preferred.
[0056] The olefinic structure A can undergo substitution reaction with active hydrogen and introduce a carbon-carbon double bond structure at the same time, and can be acryloyl chloride, allyl bromide, etc.; the amount of the olefinic structure A is: the amount ratio of the olefinic structure A to the hydroxy aromatic acid is added according to the molar ratio of halogen to hydroxyl of 1:1.
[0057] The acid-binding agent is triethylamine, potassium carbonate, etc.; the amount of the acid-binding agent used must be sufficient for the acid formed by the halogen on the basis of neutralizing the carboxyl group in the hydroxy aromatic acid; therefore, the amount of the acid-binding agent used is the sum of the molar number of the hydroxyl group and the molar number of the carboxyl group of the hydroxy aromatic acid participating in the reaction. For example: 6-hydroxy-2-naphthoic acid, allyl bromide, and acid-binding agent are added in a molar ratio of 1:1:2; or 5-amino-isophthalic acid, allyl bromide, and acid-binding agent are added in a molar ratio of 1:1:3.
[0058] S13, pass nitrogen, add intermediate product II, acrylamide, and initiator AIBN to N,N-dimethylformamide A, raise the temperature to 75-85°C, and stir for 6-10 hours; after the reaction, cool to room temperature, filter, take the filtrate, distill under reduced pressure, inject anhydrous methanol into the concentrate, stir, filter, take the insoluble matter, and place it at 60°C for vacuum drying for 6 hours to obtain intermediate product III, i.e., the first ligand;
[0059] The molar ratio of the intermediate product II to acrylamide is 0.3-0.6:0.7-0.4.
[0060] The usage ratio of the intermediate product II, N,N-dimethylformamide A and anhydrous methanol is 10 g: 150 mL: 400 mL.
[0061] S14, adding the intermediate product I to anhydrous ethanol A, ultrasonically oscillating, and dripping into N,N-dimethylformamide containing the first ligand and the second ligand at a pH of 6-7 through a peristaltic pump, stirring, controlling the temperature at 70-80°C, and reacting for 10-24 hours; cooling to room temperature, filtering, and placing the obtained solid powder into a beaker, washing with deionized water C and anhydrous ethanol B for 3 times, respectively, and drying at 80°C for 10 hours to obtain an intermediate product IV;
[0062] The first ligand and the second ligand are added in a molar ratio of 2-4:1 to participate in the coordination structure;
[0063] The intermediate product I is added in a ratio of the first ligand to the second ligand according to a molar ratio of the rare earth ion to the structure participating in the coordination of 1:8-10.
[0064] The concentration of the rare earth ion N,N-dimethylformamide solution is 0.1-0.2 mol / L;
[0065] The usage ratio of the intermediate product I, anhydrous ethanol A, deionized water C, and anhydrous ethanol B is 1g:50mL:100mL:100mL.
[0066] The second ligand includes a pyridine derivative containing active hydrogen, which may be aminoisoquinoline, hydroxyisoquinoline, etc., and preferably aminoisoquinoline, specifically 5-aminoisoquinoline.
[0067] S15, adding the intermediate product IV to dichloromethane B, performing ultrasonication to disperse, adding the olefin-containing structure B, stirring at room temperature for 2-6 hours, filtering, taking the insoluble matter, rinsing with anhydrous ethanol C for 3 times, and vacuum drying at 60° C. for 8 hours to obtain the target product, i.e., the light conversion agent;
[0068] The olefin-containing structure B is a substance that can react with active hydrogen groups and contains olefins; it can be 2-isocyanatoethyl methacrylate, glycidyl methacrylate or allyl glycidyl ether, etc.; and preferably 2-isocyanatoethyl methacrylate.
[0069] The intermediate product IV and the olefinic structure B are added in a molar ratio of active hydrogen to reactive group of 1:1.
[0070] The light conversion agent of the present invention contains zeolite, rare earth elements and a reactive structure. On the one hand, the binuclear complex formed by two rare earth ions has a cohesion effect, that is, there is energy transfer between the central ions, and the energy is concentratedly transferred to the europium ions, which greatly enhances the fluorescence intensity; on the other hand, the stability of the zeolite structure has a "confinement" effect on the rare earth ions, avoiding the loss of energy caused by the invalid vibration of the rare earth ions; thereby improving the light conversion efficiency of the light conversion agent; in addition, the energy transfer between the first ligand and the second ligand also plays an important role in improving the light conversion efficiency.
[0071] Second, the cage effect formed by the zeolite structure on rare earth ions has good stability during thermal processing and long-term use.
[0072] Third, most inorganic structures are difficult to disperse, and even those with good dispersibility still have some microscopic phase separation. The zeolite structure in the present invention is wrapped by the first ligand; at the same time, it is coordinated by the reactive second ligand to form an additive with a macromolecular organic chain as the shell, and can undergo a cross-linking reaction with the main resin, thereby further eliminating the problem of phase separation while solving the problem of dispersibility.
[0073] Therefore, applying the light conversion agent described in the present invention to the packaging film can obtain an EVA light conversion packaging film.
[0074] The embodiment of the present invention provides an EVA light-converting packaging film, comprising the following raw materials in parts by weight:
[0075] EVA resin 100 parts;
[0076] Cross-linking agent 0.8-1.2 parts;
[0077] 1.0-1.5 parts of auxiliary cross-linking agent;
[0078] 0.1-5.0 parts of light conversion agent;
[0079] Antioxidant 0.15-0.25 parts;
[0080] Light stabilizer 0.05-0.08 parts;
[0081] Coupling agent 0.3-0.5 parts.
[0082] The EVA resin described in the present invention has a VA content of 28-33%. In the following embodiments of the present invention, the EVA resin with a VA content of 33% and a melt index (MI) of 31 is preferably purchased from DuPont, USA.
[0083] The crosslinking agent in the present invention can be benzoyl peroxide, 2,5-dimethyl-2,5-bis(benzoyl peroxide)hexane, dicyclohexyl peroxycarbonate or diisopropylbenzene peroxide, etc.; the crosslinking agent in the following embodiments of the present invention is 2,5-dimethyl-2,5-bis(benzoyl peroxide)hexane.
[0084] The auxiliary cross-linking agent in the present invention is allyl and / or acryloxy.
[0085] The allyl cross-linking auxiliary agent may be triallyl cyanurate or triallyl isocyanurate.
[0086] The acryloxy-based co-crosslinking agent may be any combination of trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, propoxylated neopentyl glycol diacrylate, and pentaerythritol triacrylate.
[0087] The auxiliary cross-linking agent described in the following embodiments of the present invention is triallyl isocyanurate, trimethylolpropane trimethacrylate, propoxylated trimethylolpropane triacrylate and pentaerythritol triacrylate added in a mass ratio of 8:3:2:2.
[0088] The antioxidant described in the present invention is a combination of hindered phenols and phosphites. The hindered phenol antioxidants may be antioxidant 1010, antioxidant 1076, antioxidant 264, antioxidant 2246, etc.; and antioxidant 1010 is preferred. The phosphite antioxidants may be antioxidant 168, antioxidant 242, antioxidant TPP, etc.; and antioxidant 168 is preferred. In the following embodiments of the present invention, the antioxidants are antioxidant 1010 and antioxidant 168 added in a mass ratio of 1:2.
[0089] In the present invention, the light stabilizer is a hindered amine light stabilizer to avoid competition with the light conversion agent for ultraviolet rays. The hindered amine light stabilizer can be UV-292, UV-770 or GW540, etc., and UV-292 is preferred. In the following embodiments of the present invention, the light stabilizer is UV-292.
[0090] The coupling agent described in the following embodiments of the present invention is a silane coupling agent, specifically a vinyl silane coupling agent, which may be KH151 or KH171, etc., and KH171 is preferred.
[0091] In order to better understand the above invention, a method for preparing an EVA light-converting encapsulation film in the following embodiment of the present invention comprises the following steps:
[0092] S21, mixing, i.e.
[0093] Add the raw materials according to the formula ratio into a mixer, mix and stir at a temperature of 40° C. and a rotation speed of 80 rpm for 2 h to obtain a mixed raw material;
[0094] S22, extrusion, i.e.
[0095] The mixed raw materials in S21 are placed in a twin-screw extruder, melt-blended and extruded at a speed of 50 rpm with the temperature of the first zone being 80° C., the temperature of the second zone being 90° C., and the temperature of the third zone being 85° C., and the material is discharged through a cast film die head and cast, and cooled by a cast roller;
[0096] S23, film formation, i.e.
[0097] After thickness measurement, edge pressing, shaping, edge trimming and rolling, the anti-oxidation battery encapsulation EVA film with a thickness of 500 μm is obtained.
[0098] In order to further understand the present invention, an EVA light-converting packaging film provided by the present invention is described in detail below in conjunction with specific embodiments. The protection scope of the present invention is not limited by the following embodiments.
[0099] Example 1
[0100] A method for preparing a light conversion agent comprises the following steps:
[0101] S11, adding zeolite into a deionized water solution containing rare earth ions, stirring, heating to 80°C and reacting for 24 hours; after the reaction, filtering, taking out insoluble matter, rinsing with deionized water A, and drying at 60°C for 12 hours to obtain an intermediate product I;
[0102] The zeolite and rare earth ions are added at a molar ratio of sodium ions to rare earth ions of 25:1;
[0103] The concentration of the deionized water solution containing rare earth ions is 0.04 mol / L;
[0104] The dosage of the zeolite and deionized water A is 1 g:100 mL.
[0105] The rare earth ions are europium ions and yttrium ions in a molar ratio of 2.8:7.2.
[0106] Its infrared data is as follows: 3441cm -1 、1637cm -1 :-OH (coordinated with rare earth) broad peak exists; 1048cm -1 :-Si-O-Si- exists; 794cm -1 、724cm -1 : Silicon oxygen tetrahedron -Si-O-Si-, aluminum oxygen octahedron -Al-O-Si-.
[0107] S12, add 6-hydroxy-2-naphthoic acid and potassium carbonate to dichloromethane A, stir, add allyl bromide and hydroquinone, control the temperature at 120°C, react for 5 hours; filter, take the filtrate, wash with 20wt% dilute hydrochloric acid and deionized water B for 3 times respectively, separate the liquids, take the organic phase, dry it with anhydrous sodium sulfate, let it stand overnight, filter, take the organic phase, and rotary evaporate to obtain intermediate product II;
[0108] The usage ratio of 6-hydroxy-2-naphthoic acid, potassium carbonate, dichloromethane A, allyl bromide, 20wt% dilute hydrochloric acid, deionized water B, and anhydrous sodium sulfate is 1mmol:2mmol:100mL:1mmol:150mL, 150mL:10g;
[0109] The amount of hydroquinone used is 1.0% of the mass of allyl bromide.
[0110] Its infrared data are as follows: 3440cm -1 :-OH exists and weakens; 1780cm -1 :-C=O exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1622cm -1 :-C=C- exists; 668cm -1 :-C-Br does not exist.
[0111] S13, pass nitrogen, add intermediate product II, acrylamide, and initiator AIBN to N,N-dimethylformamide A, heat to 80°C, and stir for 8 hours; after the reaction, cool to room temperature, filter, take the filtrate, distill under reduced pressure, inject anhydrous methanol into the concentrate, stir, filter, take the insoluble matter, and place it at 60°C for vacuum drying for 6 hours to obtain intermediate product III That is, the first ligand;
[0112] The molar ratio of the intermediate product II to acrylamide is 0.4:0.6.
[0113] The usage ratio of the intermediate product II, N,N-dimethylformamide A and anhydrous methanol is 10 g: 150 mL: 400 mL.
[0114] Its infrared data are as follows: 3200-3500cm -1 :-OH, -NH2 exist; 1780cm -1 、1668cm -1 :-C=O exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1622cm -1 :-C=C- does not exist.
[0115] S14, adding the intermediate product I to anhydrous ethanol A, ultrasonically oscillating, and dripping into N,N-dimethylformamide containing the first ligand and 5-aminoisoquinoline at pH 7 through a peristaltic pump, stirring, controlling the temperature at 75°C, and reacting for 15 hours; cooling to room temperature, filtering, and placing the obtained solid powder into a beaker, washing with deionized water C and anhydrous ethanol B for 3 times, respectively, and drying at 80°C for 10 hours to obtain an intermediate product IV;
[0116] The first ligand and 5-aminoisoquinoline are added in a molar ratio of 3:1 to participate in the coordination structure;
[0117] The intermediate product I, the first ligand and 5-aminoisoquinoline are added in a molar ratio of rare earth ions to the coordination structure of 1:9.
[0118] The concentration of the rare earth ion N,N-dimethylformamide solution is 0.15 mol / L;
[0119] The usage ratio of the intermediate product I, anhydrous ethanol A, deionized water C, and anhydrous ethanol B is 1g:50mL:100mL:100mL.
[0120] Its infrared data is as follows: 3441cm -1 、1637cm -1 :-OH (coordinated with rare earth) broad peak exists; 3348cm -1 :-NH2 exists; 1761cm -1 、1655cm -1 :-C=O (coordinated with rare earth) exists; 1632cm -1 : Quinoline-C=N- (coordinated with rare earth) exists; 3011cm -1 、1595cm -1 、1498cm -1 : Benzene ring exists; 1048cm -1 :-Si-O-Si- exists; 794cm -1 、724cm -1 : Silicon oxygen tetrahedron -Si-O-Si-, aluminum oxygen octahedron -Al-O-Si-.
[0121] S15, adding the intermediate product IV to dichloromethane B, performing ultrasonication for dispersion, adding 2-isocyanatoethyl methacrylate, stirring at room temperature for 5 hours, filtering, taking the insoluble matter, rinsing with anhydrous ethanol C for 3 times, and drying under vacuum at 60° C. for 8 hours to obtain the target product, i.e., the light conversion agent;
[0122] The intermediate product IV and 2-isocyanatoethyl methacrylate are added in a molar ratio of amino group to isocyanate group of 1:1;
[0123] The usage ratio of the intermediate product IV, dichloromethane B, and anhydrous ethanol C is 1 g: 50 mL: 100 mL.
[0124] Its infrared data is as follows: 3441cm -1 、1637cm -1 :-OH (coordinated with rare earth) broad peak exists; 3346cm -1 : -NH2 exists and weakens; 1761cm -1 、1655cm -1:-C=O (coordinated with rare earth) exists; 1735cm -1 、1667cm -1 :-C=O exists; 1632cm -1 : Quinoline-C=N- (coordinated with rare earth) exists; 1609cm -1 、810cm -1 :-C=C- exists; 3011cm -1 、1595cm -1 、1498cm -1 : Benzene ring exists; 1048cm -1 :-Si-O-Si- exists; 794cm -1 、724cm -1 : Silicon oxygen tetrahedron -Si-O-Si-, aluminum oxygen octahedron -Al-O-Si-.
[0125] An EVA light-converting packaging film comprises the following raw materials in parts by weight:
[0126] EVA resin 100 parts;
[0127] 1.0 part of cross-linking agent;
[0128] 1.2 parts of auxiliary cross-linking agent;
[0129] 3.0 parts of light conversion agent;
[0130] Antioxidant 0.18 parts;
[0131] Light stabilizer 0.06 parts;
[0132] Coupling agent KH171 0.4 parts.
[0133] Example 2
[0134] The rest is the same as in Example 1, except that:
[0135] A method for preparing a light conversion agent comprises the following steps:
[0136] S11, adding zeolite into a deionized water solution containing rare earth ions, stirring, heating to 80°C and reacting for 24 hours; after the reaction, filtering, taking out insoluble matter, rinsing with deionized water A, and drying at 60°C for 12 hours to obtain an intermediate product I;
[0137] The zeolite and rare earth ions are added at a molar ratio of sodium ions to rare earth ions of 25:1;
[0138] The concentration of the deionized water solution containing rare earth ions is 0.04 mol / L;
[0139] The dosage of the zeolite and deionized water A is 1 g:100 mL.
[0140] The rare earth ions are europium ions and yttrium ions in a molar ratio of 2.8:7.2.
[0141] Its infrared data is as follows: 3441cm -1 、1637cm -1 :-OH (coordinated with rare earth) broad peak exists; 1048cm -1 :-Si-O-Si- exists; 794cm -1 、724cm -1 : Silicon oxygen tetrahedron -Si-O-Si-, aluminum oxygen octahedron -Al-O-Si-.
[0142] S12, add 6-hydroxy-2-naphthoic acid and triethylamine to dichloromethane A1, ice bath, stir, dissolve acryloyl chloride in dichloromethane A2 and place in a constant pressure dropping funnel, control the temperature at 5°C, add dropwise within 2 hours, continue to react for 12 hours; filter, take the filtrate, wash with 20wt% dilute hydrochloric acid and deionized water B for 3 times respectively, separate the liquids, take the organic phase, dry with anhydrous sodium sulfate, stand overnight, filter, take the organic phase, and rotary evaporate to obtain intermediate II;
[0143] The usage ratios of the 6-hydroxy-2-naphthoic acid, triethylamine, dichloromethane A1, acryloyl chloride, dichloromethane A2, 20wt% dilute hydrochloric acid, deionized water B, and anhydrous sodium sulfate are 1mmol:2mmol:100mL:1mmol:50mL:150mL, and 150mL:10g.
[0144] Its infrared data are as follows: 3440cm -1 :-OH exists and weakens; 1780cm -1 、1735cm -1 :-C=O exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1612cm -1 、810cm -1 :-C=C- exists; 728cm -1 :-C-Cl does not exist.
[0145] S13, pass nitrogen, add intermediate product II, acrylamide, and initiator AIBN to N,N-dimethylformamide A, heat to 80°C, and stir for 8 hours; after the reaction, cool to room temperature, filter, take the filtrate, distill under reduced pressure, inject anhydrous methanol into the concentrate, stir, filter, take the insoluble matter, and place it at 60°C for vacuum drying for 6 hours to obtain intermediate product III That is, the first ligand;
[0146] The molar ratio of the intermediate product II to acrylamide is 0.5:0.5.
[0147] The usage ratio of the intermediate product II, N,N-dimethylformamide A and anhydrous methanol is 10 g: 150 mL: 400 mL.
[0148] Its infrared data are as follows: 3200-3500cm -1 :-OH, -NH2 exist; 1780cm -1 、1735cm -1 、1668cm -1 :-C=O exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1612cm -1 、810cm -1 :-C=C- does not exist.
[0149] S14, adding the intermediate product I to anhydrous ethanol A, ultrasonically oscillating, and dripping into N,N-dimethylformamide containing the first ligand and 5-aminoisoquinoline at pH 7 through a peristaltic pump, stirring, controlling the temperature at 75°C, and reacting for 15 hours; cooling to room temperature, filtering, and placing the obtained solid powder into a beaker, washing with deionized water C and anhydrous ethanol B for 3 times, respectively, and drying at 80°C for 10 hours to obtain an intermediate product IV;
[0150] The first ligand and 5-aminoisoquinoline are added in a molar ratio of 3:1 to participate in the coordination structure;
[0151] The intermediate product I, the first ligand and 5-aminoisoquinoline are added in a molar ratio of rare earth ions to the coordination structure of 1:9.
[0152] The concentration of the rare earth ion N,N-dimethylformamide solution is 0.15 mol / L;
[0153] The usage ratio of the intermediate product I, anhydrous ethanol A, deionized water C, and anhydrous ethanol B is 1g:50mL:100mL:100mL.
[0154] Its infrared data is as follows: 3441cm -1 、1637cm -1 :-OH (coordinated with rare earth) broad peak exists; 3348cm -1 :-NH2 exists; 1761cm -1 、1655cm -1 :-C=O (coordinated with rare earth) exists; 1735cm -1 :-C=O exists; 1632cm-1 : Quinoline-C=N- (coordinated with rare earth) exists; 3011cm -1 、1595cm -1 、1498cm -1 : Benzene ring exists; 1048cm -1 :-Si-O-Si- exists; 794cm -1 、724cm -1 : Silicon oxygen tetrahedron -Si-O-Si-, aluminum oxygen octahedron -Al-O-Si-.
[0155] S15, adding the intermediate product IV to dichloromethane B, performing ultrasonication for dispersion, adding 2-isocyanatoethyl methacrylate, stirring at room temperature for 5 hours, filtering, taking the insoluble matter, rinsing with anhydrous ethanol C for 3 times, and drying under vacuum at 60° C. for 8 hours to obtain the target product, i.e., the light conversion agent;
[0156] The intermediate product IV and 2-isocyanatoethyl methacrylate are added in a molar ratio of amino group to isocyanate group of 1:1;
[0157] The usage ratio of the intermediate product IV, dichloromethane B, and anhydrous ethanol C is 1 g: 50 mL: 100 mL.
[0158] Its infrared data is as follows: 3441cm -1 、1637cm -1 :-OH (coordinated with rare earth) broad peak exists; 3346cm -1 : -NH2 exists and weakens; 1761cm -1 、1655cm -1 :-C=O (coordinated with rare earth) exists; 1735cm -1 、1667cm -1 :-C=O exists; 1632cm -1 : Quinoline-C=N- (coordinated with rare earth) exists; 1609cm -1 、810cm -1 :-C=C- exists; 3011cm -1 、1595cm -1 、1498cm -1 : Benzene ring exists; 1048cm -1 :-Si-O-Si- exists; 794cm -1 、724cm -1 : Silicon oxygen tetrahedron -Si-O-Si-, aluminum oxygen octahedron -Al-O-Si-.
[0159] Example 3
[0160] The rest is the same as in Example 1, except that:
[0161] A method for preparing a light conversion agent comprises the following steps:
[0162] S11, adding zeolite into a deionized water solution containing rare earth ions, stirring, heating to 70°C and reacting for 30 hours; after the reaction, filtering, taking out insoluble matter, rinsing with deionized water A, and drying at 60°C for 12 hours to obtain an intermediate product I;
[0163] The zeolite and rare earth ions are added at a molar ratio of sodium ions to rare earth ions of 20:1;
[0164] The concentration of the deionized water solution containing rare earth ions is 0.05 mol / L;
[0165] The dosage of the zeolite and deionized water A is 1 g:100 mL.
[0166] The rare earth ions are europium ions and yttrium ions in a molar ratio of 2.8:7.2.
[0167] Its infrared data is as follows: 3441cm -1 、1637cm -1 :-OH (coordinated with rare earth) broad peak exists; 1048cm -1 :-Si-O-Si- exists; 794cm -1 、724cm -1 : Silicon oxygen tetrahedron -Si-O-Si-, aluminum oxygen octahedron -Al-O-Si-.
[0168] S12, add 6-hydroxy-2-naphthoic acid and potassium carbonate to dichloromethane A, stir, add allyl bromide and hydroquinone, control the temperature at 110°C, react for 6 hours; filter, take the filtrate, wash with 20wt% dilute hydrochloric acid and deionized water B for 3 times respectively, separate the liquids, take the organic phase, dry it with anhydrous sodium sulfate, let it stand overnight, filter, take the organic phase, and rotary evaporate to obtain intermediate II;
[0169] The usage ratio of 6-hydroxy-2-naphthoic acid, potassium carbonate, dichloromethane A, allyl bromide, 20wt% dilute hydrochloric acid, deionized water B, and anhydrous sodium sulfate is 1mmol:2mmol:100mL:1mmol:150mL, 150mL:10g;
[0170] The amount of hydroquinone used is 1.0% of the mass of allyl bromide.
[0171] Its infrared data are as follows: 3440cm -1 :-OH exists and weakens; 1780cm -1 :-C=O exists; 3011cm -1 、1595cm -1 、1498cm-1 : benzene ring exists; 1622cm -1 :-C=C- exists; 668cm -1 :-C-Br does not exist.
[0172] S13, pass nitrogen, add intermediate product II, acrylamide, and initiator AIBN to N,N-dimethylformamide A, heat to 85°C, and stir for 6 hours; after the reaction, cool to room temperature, filter, take the filtrate, distill under reduced pressure, inject anhydrous methanol into the concentrate, stir, filter, take the insoluble matter, and place it at 60°C for 6 hours to obtain intermediate product III That is, the first ligand;
[0173] The molar ratio of the intermediate product II to acrylamide is 0.4:0.6.
[0174] The usage ratio of the intermediate product II, N,N-dimethylformamide A and anhydrous methanol is 10 g: 150 mL: 400 mL.
[0175] Its infrared data are as follows: 3200-3500cm -1 :-OH, -NH2 exist; 1780cm -1 、1668cm -1 :-C=O exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1622cm -1 :-C=C- does not exist.
[0176] S14, adding the intermediate product I to anhydrous ethanol A, ultrasonically oscillating, and dripping it into N,N-dimethylformamide containing the first ligand and 5-aminoisoquinoline at a pH of 6 through a peristaltic pump, stirring, controlling the temperature at 80°C, and reacting for 10 hours; cooling to room temperature, filtering, and placing the obtained solid powder into a beaker, washing it with deionized water C and anhydrous ethanol B for 3 times respectively, and drying it at 80°C for 10 hours to obtain an intermediate product IV;
[0177] The first ligand and 5-aminoisoquinoline are added in a molar ratio of 3:1 to participate in the coordination structure;
[0178] The intermediate product I, the first ligand and 5-aminoisoquinoline are added in a molar ratio of rare earth ions to the coordination structure of 1:9.
[0179] The concentration of the rare earth ion N,N-dimethylformamide solution is 0.1 mol / L;
[0180] The usage ratio of the intermediate product I, anhydrous ethanol A, deionized water C, and anhydrous ethanol B is 1g:50mL:100mL:100mL.
[0181] Its infrared data is as follows: 3441cm -1 、1637cm -1 :-OH (coordinated with rare earth) broad peak exists; 3348cm -1 :-NH2 exists; 1761cm -1 、1655cm -1 :-C=O (coordinated with rare earth) exists; 1632cm -1 : Quinoline-C=N- (coordinated with rare earth) exists; 3011cm -1 、1595cm -1 、1498cm -1 : Benzene ring exists; 1048cm -1 :-Si-O-Si- exists; 794cm -1 、724cm -1 : Silicon oxygen tetrahedron -Si-O-Si-, aluminum oxygen octahedron -Al-O-Si-.
[0182] S15, adding the intermediate product IV to dichloromethane B, performing ultrasonication for dispersion, adding 2-isocyanatoethyl methacrylate, stirring at room temperature for 2 hours, filtering, taking out the insoluble matter, rinsing with anhydrous ethanol C for 3 times, and drying under vacuum at 60° C. for 8 hours to obtain the target product, i.e., the light conversion agent;
[0183] The intermediate product IV and 2-isocyanatoethyl methacrylate are added in a molar ratio of amino group to isocyanate group of 1:1;
[0184] The usage ratio of the intermediate product IV, dichloromethane B, and anhydrous ethanol C is 1 g: 50 mL: 100 mL.
[0185] Its infrared data is as follows: 3441cm -1 、1637cm -1 :-OH (coordinated with rare earth) broad peak exists; 3346cm -1 : -NH2 exists and weakens; 1761cm -1 、1655cm -1 :-C=O (coordinated with rare earth) exists; 1735cm -1 、1667cm -1 :-C=O exists; 1632cm -1 : Quinoline-C=N- (coordinated with rare earth) exists; 1609cm -1 、810cm -1 :-C=C- exists; 3011cm -1、1595cm -1 、1498cm -1 : Benzene ring exists; 1048cm -1 :-Si-O-Si- exists; 794cm -1 、724cm -1 : Silicon oxygen tetrahedron -Si-O-Si-, aluminum oxygen octahedron -Al-O-Si-.
[0186] Example 4
[0187] The rest is the same as in Example 1, except that:
[0188] A method for preparing a light conversion agent comprises the following steps:
[0189] S11, adding zeolite into a deionized water solution containing rare earth ions, stirring, heating to 90°C and reacting for 20 hours; after the reaction, filtering, taking out insoluble matter, rinsing with deionized water A, and drying at 60°C for 12 hours to obtain an intermediate product I;
[0190] The zeolite and rare earth ions are added at a molar ratio of sodium ions to rare earth ions of 30:1;
[0191] The concentration of the deionized water solution containing rare earth ions is 0.03 mol / L;
[0192] The dosage of the zeolite and deionized water A is 1 g:100 mL.
[0193] The rare earth ions are europium ions and yttrium ions in a molar ratio of 2.8:7.2.
[0194] Its infrared data is as follows: 3441cm -1 、1637cm -1 :-OH (coordinated with rare earth) broad peak exists; 1048cm -1 :-Si-O-Si- exists; 794cm -1 、724cm -1 : Silicon oxygen tetrahedron -Si-O-Si-, aluminum oxygen octahedron -Al-O-Si-.
[0195] S12, add 6-hydroxy-2-naphthoic acid and potassium carbonate to dichloromethane A, stir, add allyl bromide and hydroquinone, control the temperature at 125°C, react for 4 hours; filter, take the filtrate, wash with 20wt% dilute hydrochloric acid and deionized water B for 3 times respectively, separate the liquids, take the organic phase, dry it with anhydrous sodium sulfate, let it stand overnight, filter, take the organic phase, and rotary evaporate to obtain intermediate II;
[0196] The usage ratio of 6-hydroxy-2-naphthoic acid, potassium carbonate, dichloromethane A, allyl bromide, 20wt% dilute hydrochloric acid, deionized water B, and anhydrous sodium sulfate is 1mmol:2mmol:100mL:1mmol:150mL, 150mL:10g;
[0197] The amount of hydroquinone used is 1.0% of the mass of allyl bromide.
[0198] Its infrared data are as follows: 3440cm -1 :-OH exists and weakens; 1780cm -1 :-C=O exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1622cm -1 :-C=C- exists; 668cm -1 :-C-Br does not exist.
[0199] S13, pass nitrogen, add intermediate product II, acrylamide, and initiator AIBN to N,N-dimethylformamide A, raise the temperature to 75°C, and stir for 10 hours; after the reaction, cool to room temperature, filter, take the filtrate, distill under reduced pressure, inject anhydrous methanol into the concentrate, stir, filter, take the insoluble matter, and place it at 60°C for vacuum drying for 6 hours to obtain intermediate product III That is, the first ligand;
[0200] The molar ratio of the intermediate product II to acrylamide is 0.4:0.6.
[0201] The usage ratio of the intermediate product II, N,N-dimethylformamide A and anhydrous methanol is 10 g: 150 mL: 400 mL.
[0202] Its infrared data are as follows: 3200-3500cm -1 :-OH, -NH2 exist; 1780cm -1 、1668cm -1 :-C=O exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1622cm -1 :-C=C- does not exist.
[0203] S14, adding the intermediate product I to anhydrous ethanol A, ultrasonically oscillating, and dripping it into N,N-dimethylformamide containing the first ligand and 5-aminoisoquinoline at a pH of 7 through a peristaltic pump, stirring, controlling the temperature at 70°C, and reacting for 24 hours; cooling to room temperature, filtering, and placing the obtained solid powder into a beaker, washing it with deionized water C and anhydrous ethanol B for 3 times respectively, and drying it at 80°C for 10 hours to obtain an intermediate product IV;
[0204] The first ligand and 5-aminoisoquinoline are added in a molar ratio of 3:1 to participate in the coordination structure;
[0205] The intermediate product I, the first ligand and 5-aminoisoquinoline are added in a molar ratio of rare earth ions to the coordination structure of 1:9.
[0206] The concentration of the rare earth ion N,N-dimethylformamide solution is 0.2 mol / L;
[0207] The usage ratio of the intermediate product I, anhydrous ethanol A, deionized water C, and anhydrous ethanol B is 1g:50mL:100mL:100mL.
[0208] Its infrared data is as follows: 3441cm -1 、1637cm -1 :-OH (coordinated with rare earth) broad peak exists; 3348cm -1 :-NH2 exists; 1761cm -1 、1655cm -1 :-C=O (coordinated with rare earth) exists; 1632cm -1 : Quinoline-C=N- (coordinated with rare earth) exists; 3011cm -1 、1595cm -1 、1498cm -1 : Benzene ring exists; 1048cm -1 :-Si-O-Si- exists; 794cm -1 、724cm -1 : Silicon oxygen tetrahedron -Si-O-Si-, aluminum oxygen octahedron -Al-O-Si-.
[0209] S15, adding the intermediate product IV to dichloromethane B, performing ultrasonication for dispersion, adding 2-isocyanatoethyl methacrylate, stirring at room temperature for 6 hours, filtering, taking the insoluble matter, rinsing with anhydrous ethanol C for 3 times, and drying under vacuum at 60° C. for 8 hours to obtain the target product, i.e., the light conversion agent;
[0210] The intermediate product IV and 2-isocyanatoethyl methacrylate are added in a molar ratio of amino group to isocyanate group of 1:1;
[0211] The usage ratio of the intermediate product IV, dichloromethane B, and anhydrous ethanol C is 1 g: 50 mL: 100 mL.
[0212] Its infrared data is as follows: 3441cm -1 、1637cm -1 :-OH (coordinated with rare earth) broad peak exists; 3346cm -1 : -NH2 exists and weakens; 1761cm -1 、1655cm -1 :-C=O (coordinated with rare earth) exists; 1735cm -1 、1667cm -1 :-C=O exists; 1632cm -1 : Quinoline-C=N- (coordinated with rare earth) exists; 1609cm -1 、810cm -1 :-C=C- exists; 3011cm -1 、1595cm -1 、1498cm -1 : Benzene ring exists; 1048cm -1 :-Si-O-Si- exists; 794cm -1 、724cm -1 : Silicon oxygen tetrahedron -Si-O-Si-, aluminum oxygen octahedron -Al-O-Si-.
[0213] Example 5
[0214] The rest is the same as in Example 1, except that:
[0215] A method for preparing a light conversion agent, wherein in step S11,
[0216] The yttrium ions are replaced with cerium ions.
[0217] Example 6
[0218] The rest is the same as in Example 1, except that:
[0219] A method for preparing a light conversion agent, wherein in step S11,
[0220] The rare earth ions are europium ions and yttrium ions in a molar ratio of 2.0:8.0.
[0221] Example 7
[0222] The rest is the same as in Example 1, except that:
[0223] A method for preparing a light conversion agent, wherein in step S11,
[0224] The rare earth ions are europium ions and yttrium ions in a molar ratio of 3.0:7.0.
[0225] Example 8
[0226] The rest is the same as in Example 1, except that:
[0227] A method for preparing a light conversion agent, wherein in step S13,
[0228] The molar ratio of the intermediate product II to acrylamide is 0.3:0.7.
[0229] Example 9
[0230] The rest is the same as in Example 1, except that:
[0231] A method for preparing a light conversion agent, wherein in step S13,
[0232] The molar ratio of the intermediate product II to acrylamide is 0.6:0.4.
[0233] Example 10
[0234] The rest is the same as in Example 1, except that:
[0235] A method for preparing a light conversion agent, wherein in step S14,
[0236] The first ligand and 5-aminoisoquinoline are added in a molar ratio of 2:1 to participate in the coordination structure; and
[0237] The intermediate product I, the first ligand and 5-aminoisoquinoline are added in a molar ratio of rare earth ions to the coordination structure of 1:8.
[0238] Embodiment 11
[0239] The rest is the same as in Example 1, except that:
[0240] A method for preparing a light conversion agent, wherein in step S14,
[0241] The first ligand and 5-aminoisoquinoline are added in a molar ratio of 4:1 to participate in the coordination structure; and
[0242] The intermediate product I, the first ligand and 5-aminoisoquinoline are added in a ratio of rare earth ions to the coordination structure of 1:10.
[0243] Example 12
[0244] The rest is the same as in Example 1, except that:
[0245] An EVA light-converting packaging film comprises the following raw materials in parts by weight:
[0246] EVA resin 100 parts;
[0247] 0.8 part of cross-linking agent;
[0248] 1.5 parts of auxiliary cross-linking agent;
[0249] 3.0 parts of light conversion agent;
[0250] 0.25 parts of antioxidant;
[0251] Light stabilizer 0.05 parts;
[0252] Coupling agent KH171 0.5 parts.
[0253] Embodiment 13
[0254] The rest is the same as in Example 1, except that:
[0255] An EVA light-converting packaging film comprises the following raw materials in parts by weight:
[0256] EVA resin 100 parts;
[0257] 1.2 parts of cross-linking agent;
[0258] 1.0 part of auxiliary cross-linking agent;
[0259] 3.0 parts of light conversion agent;
[0260] 0.15 parts of antioxidant;
[0261] Light stabilizer 0.08 parts;
[0262] Coupling agent KH171 0.3 parts.
[0263] Embodiment 14
[0264] The rest is the same as in Example 1, except that:
[0265] An EVA light-converting packaging film comprises the following raw materials in parts by weight:
[0266] EVA resin 100 parts;
[0267] 1.0 part of cross-linking agent;
[0268] 1.2 parts of auxiliary cross-linking agent;
[0269] 0.1 part of light conversion agent;
[0270] Antioxidant 0.18 parts;
[0271] Light stabilizer 0.06 parts;
[0272] Coupling agent KH171 0.4 parts.
[0273] Embodiment 15
[0274] The rest is the same as in Example 1, except that:
[0275] An EVA light-converting packaging film comprises the following raw materials in parts by weight:
[0276] EVA resin 100 parts;
[0277] 1.0 part of cross-linking agent;
[0278] 1.2 parts of auxiliary cross-linking agent;
[0279] 5.0 parts of light conversion agent;
[0280] Antioxidant 0.18 parts;
[0281] Light stabilizer 0.06 parts;
[0282] Coupling agent KH171 0.4 parts.
[0283] The EVA light-converting packaging films in the following comparative examples are compared with Example 1:
[0284] Comparative Example 1
[0285] An EVA light-converting packaging film comprises the following raw materials in parts by weight:
[0286] EVA resin 100 parts;
[0287] 1.0 part of cross-linking agent;
[0288] 1.2 parts of auxiliary cross-linking agent;
[0289] Antioxidant 0.18 parts;
[0290] Light stabilizer 0.06 parts;
[0291] Coupling agent KH171 0.4 parts.
[0292] Comparative Example 2
[0293] The rest is the same as in Example 1, except that:
[0294] A method for preparing a light conversion agent comprises the following steps:
[0295] S11, add 6-hydroxy-2-naphthoic acid and potassium carbonate to dichloromethane A, stir, add allyl bromide and hydroquinone, control the temperature at 120°C, react for 5 hours; filter, take the filtrate, wash with 20wt% dilute hydrochloric acid and deionized water B for 3 times respectively, separate the liquids, take the organic phase, dry it with anhydrous sodium sulfate, let it stand overnight, filter, take the organic phase, and rotary evaporate to obtain intermediate product I;
[0296] The usage ratio of 6-hydroxy-2-naphthoic acid, potassium carbonate, dichloromethane A, allyl bromide, 20wt% dilute hydrochloric acid, deionized water B, and anhydrous sodium sulfate is 1mmol:2mmol:100mL:1mmol:150mL, 150mL:10g;
[0297] The amount of hydroquinone used is 1.0% of the mass of allyl bromide.
[0298] Its infrared data are as follows: 3440cm -1 :-OH exists and weakens; 1780cm -1 :-C=O exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1622cm -1 :-C=C- exists; 668cm -1 :-C-Br does not exist.
[0299] S12, pass nitrogen, add intermediate product I, acrylamide, and initiator AIBN to N,N-dimethylformamide A, heat to 80°C, and stir for 8 hours; after the reaction, cool to room temperature, filter, take the filtrate, distill under reduced pressure, inject anhydrous methanol into the concentrate, stir, filter, take the insoluble matter, and place it at 60°C for vacuum drying for 6 hours to obtain intermediate product II That is, the first ligand;
[0300] The molar ratio of the intermediate product I to acrylamide is 0.4:0.6.
[0301] The usage ratio of the intermediate product I, N,N-dimethylformamide A and anhydrous methanol is 10g:150mL:400mL.
[0302] Its infrared data are as follows: 3200-3500cm -1 :-OH, -NH2 exist; 1780cm -1 、1668cm -1 :-C=O exists; 3011cm -1 、1595cm -1 、1498cm -1 : benzene ring exists; 1622cm -1 :-C=C- does not exist.
[0303] S13, adding rare earth ions to anhydrous ethanol A, ultrasonically oscillating, and dripping into N,N-dimethylformamide containing the first ligand and 5-aminoisoquinoline at pH 7 through a peristaltic pump, stirring, controlling the temperature at 75°C, and reacting for 15 hours; cooling to room temperature, filtering, and placing the obtained solid powder into a beaker, washing with deionized water C and anhydrous ethanol B for 3 times, respectively, and drying at 80°C for 10 hours to obtain an intermediate product III;
[0304] The first ligand and 5-aminoisoquinoline are added in a molar ratio of 3:1 to participate in the coordination structure;
[0305] The rare earth ion, the first ligand and 5-aminoisoquinoline are added at a molar ratio of the rare earth ion to the coordination structure of 1:9.
[0306] The rare earth ions are europium ions.
[0307] The concentration of the rare earth ion N,N-dimethylformamide solution is 0.15 mol / L;
[0308] The usage ratio of the rare earth ion, anhydrous ethanol A, deionized water C, and anhydrous ethanol B is 1g:50mL:100mL:100mL.
[0309] Its infrared data is as follows: 3441cm -1 、1637cm -1 :-OH (coordinated with rare earth) broad peak exists; 3348cm -1 :-NH2 exists; 1761cm -1 、1655cm -1 :-C=O (coordinated with rare earth) exists; 1632cm -1 : Quinoline-C=N- (coordinated with rare earth) exists; 3011cm -1 、1595cm -1 、1498cm -1 : Benzene ring exists.
[0310] S14, adding the intermediate III to dichloromethane B, performing ultrasonication for dispersion, adding 2-isocyanatoethyl methacrylate, stirring at room temperature for 5 hours, filtering, taking the insoluble matter, rinsing with anhydrous ethanol C for 3 times, and drying under vacuum at 60° C. for 8 hours to obtain the target product, i.e., the light conversion agent;
[0311] The intermediate product III and 2-isocyanatoethyl methacrylate are added in a molar ratio of amino group to isocyanate group of 1:1;
[0312] The usage ratio of the intermediate product III, dichloromethane B, and anhydrous ethanol C is 1 g: 50 mL: 100 mL.
[0313] Its infrared data is as follows: 3441cm -1 、1637cm -1 :-OH (coordinated with rare earth) broad peak exists; 3346cm -1 : -NH2 exists and weakens; 1761cm -1 、1655cm -1 :-C=O (coordinated with rare earth) exists; 1735cm -1 、1667cm -1 :-C=O exists; 1632cm -1 : Quinoline-C=N- (coordinated with rare earth) exists; 1609cm -1 、810cm -1 :-C=C- exists; 3011cm -1 、1595cm -1 、1498cm -1 : Benzene ring exists.
[0314] Comparative Example 3
[0315] The rest is the same as in Comparative Example 2, except that:
[0316] The rare earth ions are europium ions and yttrium ions in a molar ratio of 2.8:7.2.
[0317] Comparative Example 4
[0318] The rest is the same as in Example 1, except that:
[0319] A method for preparing a light conversion agent, wherein in S11,
[0320] The rare earth ions are yttrium ions.
[0321] Comparative Example 5
[0322] The rest is the same as in Example 1, except that:
[0323] A method for preparing a light conversion agent, wherein in S11,
[0324] The rare earth ions are europium ions.
[0325] Comparative Example 6
[0326] The rest is the same as in Example 1, except that:
[0327] A method for preparing a light conversion agent, wherein in S14,
[0328] The first ligand and 5-aminoisoquinoline are added at a molar ratio of 0:1 for participating in the coordination structure; that is, the first ligand is not added.
[0329] Comparative Example 7
[0330] The rest is the same as in Example 1, except that:
[0331] A method for preparing a light conversion agent, wherein in S13,
[0332] The molar ratio of the intermediate product II to acrylamide is 0:0.6; that is, no intermediate product II is added.
[0333] Comparative Example 8
[0334] The rest is the same as in Example 1, except that:
[0335] A method for preparing a light conversion agent, wherein in S13,
[0336] The molar ratio of the intermediate product II to acrylamide is 0.4:0, that is, no acrylamide is added.
[0337] Comparative Example 9
[0338] The rest is the same as in Example 1, except that:
[0339] A method for preparing a light conversion agent, wherein in S14,
[0340] The first ligand and 5-aminoisoquinoline are added in a molar ratio of 3:0 to participate in the coordination structure; that is, 5-aminoisoquinoline is not added; and the intermediate product IV is the target product.
[0341] Comparative Example 10
[0342] The rest is the same as in Example 1, except that:
[0343] A method for preparing a light conversion agent,
[0344] The intermediate product IV is the target product.
[0345] The physical properties of the EVA films prepared in Examples 1-15 and Comparative Examples 1-10 of the present invention were measured respectively, and the results are shown in Table 1.
[0346] Table 1 Physical test performance of each embodiment
[0347]
[0348] First, it can be concluded from Examples 1-15 in Table 1 that the EVA light-converting encapsulation film of the present invention has obvious advantages in improving the photoelectric conversion efficiency and other performances, and at the same time has better optical properties, that is, has better compatibility.
[0349] Second, it can be observed from Example 1 and Comparative Example 1 that the EVA film of the present invention uses a self-made light conversion agent to improve the photoelectric conversion efficiency and anti-ultraviolet aging performance.
[0350] Third, from Example 1 and Comparative Examples 2-5, it can be observed that the EVA film in the present invention uses a self-made light conversion agent; the zeolite structure in the light conversion agent has the function of dispersing, adsorbing, and anchoring rare earth ions, and has a fluorescence enhancement effect; at the same time, zeolite is an inorganic non-metallic material with high heat resistance and hydrolysis resistance, and has a good protective effect on rare earth ions. The combination of two rare earth ions has a stronger fluorescence intensity and a greater power gain.
[0351] Fourth, it can be observed from Example 1 and comparative examples 6-10 that in the EVA film of the present invention, the first ligand and the pyridine derivative ligand not only provide high fluorescence intensity as ligands, but also serve as organic structures to improve compatibility with the EVA resin, thereby improving the optical performance.
[0352] In summary, the EVA light conversion packaging film of the present invention uses a self-made light conversion agent and has excellent optical properties, as well as long-lasting fluorescence intensity and power gain functions.
[0353] The test method is as follows:
[0354] (1) Light transmittance: Tested according to the method described in GB / T 29848-2013 “Ethylene-vinyl acetate copolymer (EVA) adhesive film for photovoltaic module encapsulation”.
[0355] (2) Fluorescence intensity: Test the fluorescence excitation emission spectrum (λ ex =285nm) and fluorescence quantum yield. The scanning rate is 1200nm / min, and the grating is 3nm. The fluorescence quantum yield of the EVA film prepared in Comparative Example 2 at 618nm is used as a benchmark and recorded as "1".
[0356] (3) Resistance to humidity and heat aging: The EVA film was subjected to a humidity and heat aging test. Conditions: Test conditions: +85°C, relative humidity 85%.
[0357] The test was carried out before and after, and the retention rate was calculated according to the following formula:
[0358] Retention rate = average value after the test / average value before the test × 100%.
[0359] (4) UV aging resistance: The obtained EVA film was subjected to UV irradiation aging test according to the requirements of the International Electrotechnical Commission standard IEC61345. Test conditions: the surface temperature of the test piece is 60±5℃, the UV wavelength range is 280-400nm, and the irradiation intensity is 15kW·h / m 2 , the UV irradiation test time is 2000hr.
[0360] The visible light transmittance before and after the test was measured, and the visible light transmittance retention rate was calculated according to the following formula:
[0361] Retention rate of visible light transmittance=average light transmittance after the test / average light transmittance before the test×100%.
[0362] (5) Photoelectric gain: Measured using an EL tester. Stack the photovoltaic glass, adhesive film, solar cell, adhesive film and photovoltaic backplane neatly from top to bottom, laminate at 140℃ for 15 minutes, take out and cool, first test the bare chip power and record it as P 0.1 ; The power of the component obtained by laminating the EVA film without adding adsorbent is tested and recorded as P1; the power of the new bare chip is tested and recorded as P 0.2 , the EVA film of the present invention is used for lamination, and its power is tested and recorded as P2, then the power gain P m =(P2 / P 0.2 ) / (P1 / P 0.1 ).
[0363] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. An EVA light-converting packaging film, characterized in that: The invention comprises the following raw materials in parts by weight: EVA resin 100 parts; Cross-linking agent 0.8-1.2 parts; 1.0-1.5 parts of auxiliary cross-linking agent; 0.1-5.0 parts of light conversion agent; Antioxidant 0.15-0.25 parts; Light stabilizer 0.05-0.08 parts; Coupling agent 0.3-0.5 parts; The preparation method of the light conversion agent comprises the following steps: S11, performing an ion exchange reaction between zeolite and rare earth ions to obtain an intermediate product I; S12, coupling the hydroxy aromatic acid with the olefin structure A to obtain an intermediate product II; S13, subjecting the intermediate product II to acrylamide for free radical polymerization to obtain an intermediate product III, i.e., the first ligand; S14, performing coordination reaction on the intermediate product I, the first ligand, and the second ligand to obtain an intermediate product IV; and S15, coupling reaction of the intermediate product IV with the olefin-containing structure B to obtain the target product, i.e., the light conversion agent; The zeolite and rare earth ions are added in a molar ratio of sodium ions to rare earth ions of 20-30:1; The rare earth ions are europium ions and other rare earth ions in a molar ratio of 2.0-3.0:7.0-8.0; The other rare earth ions include yttrium ions or cerium ions; The olefinic structure A is an olefinic compound containing a group that can react with a hydroxyl group; The molar ratio of the intermediate product II to acrylamide is 0.3-0.6:0.7-0.4; The first ligand and the second ligand are added in a molar ratio of 2-4:1 to participate in the coordination structure; and The intermediate product I, the first ligand, and the second ligand are added in a molar ratio of rare earth ions to the coordination structure of 1:8-10; The second ligand includes a pyridine derivative containing active hydrogen; The olefin-containing structure B is a substance that can react with active hydrogen groups and contains olefins.
2. The EVA light-converting encapsulation film according to claim 1, characterized in that: The particle size of the zeolite is 0.1-1.0 μm.
3. The method for preparing the EVA light-converting encapsulation film according to claim 1 or 2, characterized in that: The steps include: S21, mixing, i.e. Adding raw materials into a mixer according to the formula ratio, mixing and stirring to obtain mixed raw materials; S22, extrusion, i.e. The mixed raw materials in S21 are placed in an extruder for melt blending, extrusion, casting, and cooling; as well as S23, film formation, i.e. After thickness measurement, edge pressing, shaping, edge trimming and rolling, the EVA light-converting packaging film is obtained.
Citation Information
Patent Citations
Ultraviolet-resistant battery packaging EVA (Ethylene Vinyl Acetate) adhesive film
CN117210142A